Underpredicted ENSO Teleconnections in Seasonal Forecasts. Issue 5 (7th March 2023) - Williams, N. C.; Scaife, A. A.; Screen, J. A.
Abstract: The El Niño‐Southern Oscillation (ENSO) influences climate variability across the globe. ENSO is highly predictable on seasonal timescales and therefore its teleconnections are a source of extratropical forecast skill. To fully harness this predictability, teleconnections must be represented accurately in seasonal forecasts. We find that a multimodel ensemble from five seasonal forecast systems can successfully capture the spatial structure of the late winter (JFM) El Niño teleconnection to the North Atlantic via North America, but the simulated amplitude is half of that observed. We find that weak amplitude teleconnections exist in all five models throughout the troposphere, and that the La Niña teleconnection is also weak. We find evidence that tropical forcing of the El Niño teleconnection is not underestimated and instead, deficiencies are likely to emerge in the extratropics. We investigate the impact of underestimated teleconnection strength on North Atlantic winter predictability, including its relevance to the signal‐to‐noise paradox. Plain Language Summary: The El Niño‐Southern Oscillation (ENSO) describes the cycle of warmer and cooler sea surface temperatures in the tropical Pacific Ocean, which influences climate around the globe. The high heat capacity of the ocean means that ENSO changes relatively slowly and so the ENSO phase—known as El Niño or La Niña—can be predicted with high accuracy several months ahead. Far‐flung influences—known as teleconnections—of ENSO can provide predictability away from the tropics in seasonal forecasts if they are accurately modeled. In this work, the late winter (January–March) ENSO teleconnection to the North Atlantic, traveling via the North Pacific and North America, is investigated in five forecast models. We find that in each model, the pattern of the teleconnection is accurately captured, but the strength of the modeled teleconnection is half of that in the real world. We find that the strength of processes in the tropics which cause the El Niño teleconnection—including changes in sea surface temperatures and rainfall—are not underestimated by models, meaning that the problem arises further along the pathway to the extratropics. This error likely contributes to the currently unresolved "signal to noise paradox" in climate forecasts. Key Points: Seasonal forecasts severely underestimate the response to El Niño‐Southern Oscillation (ENSO) in the extratropical North Pacific The underestimated model response exists throughout the troposphere and is present for both El Niño and La Niña Tropical processes which generate the El Niño teleconnection are well predicted and so the error does not appear to originate in the tropics